Association of healthy eating index-2015 and overactive bladder: a cross-sectional study - Hao, Xuanyu; Liu, Gang; Li, Dongyang (Frontiers in Nutrition, 2024)
Objective: The aim of this cross-sectional study was to investigate the association of HEI-2015 and overactive bladder (OAB) in a large population. Methods: Data was retrieved from the National Health and Nutrition Examination Survey (NHANES) 2005-2020 datasets. Univariate and multivariate logistic regression were performed to evaluate the association between HEI-2015 and OAB. The restricted cubic spline (RCS) model was conducted to investigate the dose-response relationship. Results: Totally, this study included 29,206 participants with 6,184 OAB patients among them. The higher continuous HEI-2015 value was independently associated with lower OAB incidence (OR: 0.87; 95%CI: 0.78, 0.98). Similarly, the highest quartile categorical HEI-2015 was significantly associated with a lower OAB odds (OR:0.72; 95%CI:0.52, 0.99) when compared with the lowest quartile. The RCS curve also showed a favourable non-linear dose-response relationship between HEI-2015 and OAB. Conclusions: A higher HEI-2015 had an favorable association with OAB and there was a non-linear dose-response relationship between them. We suggest adherence to the US diet recommendation as a potential behavioral prevention of OAB. Large-scale long term prospective cohort studies across various regions are needed to verify the findings of this paper.